Influence of Ethno-Religious Identity on Voting Behaviour in 2023 Gubernatorial Election in Lagos State, Nigeria - Orunbon, Nurudeen Olalekan; Babatunde Moshood, Abdul-Wasi (Journal of World Science, 2023)
This research investigate the influence of ethno-religious identity on voting behaviour in 2023 gubernatorial election in Lagos State. Survey research design was used in conducting the research as such questionnaire was administered in collecting information from the respondents. The study population consists of all residents in Lagos East Senatorial District, Lagos State. A sample of 200 respondents was selected. Data were analyzed using Pearson Product Moment Correlation (PPMC) statistical method to analyse the formulated hypotheses. Findings from this study revealed  that there is significant relationship between ethnic identity and voting behaviour in 2023 gubernatorial election in Lagos State, (r = .783; N=200; p< .05) and also there is significant relationship between religious identity and voting behaviour in 2023 gubernatorial election in Lagos State, (r = .719; N=200; p< .05) In conclusion, the study has shown that ethnicity and religion do influence the voting behaviours in the 2023 gubernatorial election in Lagos state and analysis of the vote showed that there was variation in the voting patterns of the people as is tilted towards ethnic and religious inclination. Finally, the study recommended, The winner of 2023 governorship election should form all ethnic inclusive government and ensures that no ethnic group would complain of marginalization and also the government should sustain unity among ethnic group in Lagos State and discourage disunity.